Systolic Blood Pressure Reduction and Acute Kidney Injury in Intracerebral Hemorrhage - Qureshi, Adnan I; Huang, Wei; Lobanova, Iryna; Hanley, Daniel F; Hsu, Chung Y; Malhotra, Kunal; Steiner, Thorsten; Suarez, Jose I; Toyoda, Kazunori; Yamamoto, Haruko (Stroke (1970), 2020)
We determined the rates and predictors of acute kidney injury (AKI) and renal adverse events (AEs), and effects of AKI and renal AEs on death or disability in patients with intracerebral hemorrhage.BACKGROUND AND PURPOSEWe determined the rates and predictors of acute kidney injury (AKI) and renal adverse events (AEs), and effects of AKI and renal AEs on death or disability in patients with intracerebral hemorrhage.We analyzed data from a multicenter trial which randomized 1000 intracerebral hemorrhage patients with initial systolic blood pressure ≥180 mm Hg to intensive (goal 110-139 mm Hg) over standard (goal 140-179 mm Hg) systolic blood pressure reduction within 4.5 hours of symptom onset. AKI was identified by serial assessment of daily serum creatinine for 3 days post randomization.METHODSWe analyzed data from a multicenter trial which randomized 1000 intracerebral hemorrhage patients with initial systolic blood pressure ≥180 mm Hg to intensive (goal 110-139 mm Hg) over standard (goal 140-179 mm Hg) systolic blood pressure reduction within 4.5 hours of symptom onset. AKI was identified by serial assessment of daily serum creatinine for 3 days post randomization.AKI and renal AEs were observed in 149 patients (14.9%) and 65 patients (6.5%) among 1000 patients, respectively. In multivariate analysis, the higher baseline serum creatinine (≥110 μmol/L) was associated with AKI (odds ratio 2.4 [95% CI, 1.2-4.5]) and renal AEs (odds ratio 3.1 [95% CI, 1.2-8.1]). Higher area under the curve for intravenous nicardipine dose was associated with AKI (odds ratio 1.003 [95% CI, 1.001-1.005]) and renal AEs (odds ratio 1.003 [95% CI, 1.001-1.006]). There was a higher risk to death (relative risk 2.6 [95% CI, 1.6-4.2]) and death or disability (relative risk 1.5 [95% CI, 1.3-1.8]) at 90 days in patients with AKI but not in those with renal AEs.RESULTSAKI and renal AEs were observed in 149 patients (14.9%) and 65 patients (6.5%) among 1000 patients, respectively. In multivariate analysis, the higher baseline serum creatinine (≥110 μmol/L) was associated with AKI (odds ratio 2.4 [95% CI, 1.2-4.5]) and renal AEs (odds ratio 3.1 [95% CI, 1.2-8.1]). Higher area under the curve for intravenous nicardipine dose was associated with AKI (odds ratio 1.003 [95% CI, 1.001-1.005]) and renal AEs (odds ratio 1.003 [95% CI, 1.001-1.006]). There was a higher risk to death (relative risk 2.6 [95% CI, 1.6-4.2]) and death or disability (relative risk 1.5 [95% CI, 1.3-1.8]) at 90 days in patients with AKI but not in those with renal AEs.Intracerebral hemorrhage patients with higher baseline serum creatinine and those receiving higher doses of nicardipine were at higher risk for AKI and renal AEs. Occurrence of AKI was associated higher rates of death or disability at 3 months. Registration: URL: https://clinicaltrials.gov. Unique identifier: NCT01176565.CONCLUSIONSIntracerebral hemorrhage patients with higher baseline serum creatinine and those receiving higher doses of nicardipine were at higher risk for AKI and renal AEs. Occurrence of AKI was associated higher rates of death or disability at 3 months. Registration: URL: https://clinicaltrials.gov. Unique identifier: NCT01176565.